Perancangan Aplikasi Android Pembentukan Karakter Taruna Tingkat I PIP Semarang - Mohammad Sapta Heriyawan; Janny Andriani Djari (Politeknik Harapan Bersama, 2021)
The existence of the Covid-19 pandemic has resulted in the PIP Semarang Level I cadet education process being carried out online, including the formation of cadet character. This study presents an approach in growing and shaping the character of the Level I PIP Semarang cadets with android-based application media. The character building application is made to instill character values that must exist in PIP Semarang Level I cadets in order to build a nation with Indonesian character. With this android-based application, it can assist in creating, converting, storing, communicating and disseminating information that will be developed as a model for Taruna Character Education at the Semarang Shipping Science Polytechnic. Development using the waterfall method and testing using blackbox. Based on the results of the blackbox test, it can be said that the test results can be said to have worked well and correctly with an increase in the overall weighted average value before and after system development with a difference of 1.45